Increasing Interest In Beginning Reading In Class 1 Students Of Primary School Negeri 2 Pundungsari By Using Word Card Media - Ariyani, Ariyani (Universitas Sebelas Maret, 2022)
This research aims to increase interest in beginning reading using word card media in class I students at SD Negeri 2 Pundungsari. This type of research is Classroom Action Research which is carried out in two cycles. Each stage of the cycle is planning, implementation, observation and reflection. The data collection techniques used were 1) oral reading test and written reading comprehension test, 2) observation, and 3) documentation. Based on the research results, it shows that learning to read initially using word cards as a medium can increase the reading interest of class I students at SD Negeri 2 Pundungsari. The average reading interest score in the pre-cycle was 65 and 41.67% completeness, in the first cycle it increased to 76.25 with 75% completeness, and in the second cycle it increased to 83.33 with 100% completeness. In this action, students' interest in reading with pronunciation, intonation and reading comprehension increases until they reach the predetermined criteria for completeness, namely 60. In cycle I, word cards are used with a size of 13 x 6 cm and each word is in one color, in cycle II word cards are used. the larger one, namely 18 x 6 cm and each word has word fragments separated by different colors